Assessing the Psychological Adaptation of Kindergarten Teachers in Halabja Province - Mihraban Hussein Salih; Shirin Salih Mohammed Amin; Sozan Salar Omer; Shaima Aziz Hassan; Sozyar Nawroz Kamal (Engiscience Publisher, 2023)
This research investigates the realm of psychological adaptation, a critical aspect of the human experience that profoundly influences our daily lives, especially as we navigate the complexities of work and existence. Employing a descriptive methodology and quantitative techniques, data was collected from 166 kindergarten teachers in Halabja province, Kurdistan, Iraq, comprising both private and public educational institutions. The Statistical Package for the Social Sciences (SPSS) was used for data analysis, deploying a T-Test to scrutinize disparities in average scores between two groups and a One-way ANOVA for comparisons across multiple groups. The findings reveal that there are no statistically significant gender differences in the mental adaptation of kindergarten teachers in Halabja Province. However, a marginally significant mean difference (3.688, p = 0.058) is noted between the 20 - 29 and 30 - 39 age groups, suggesting a potential trend in mental adaptation levels among these age categories. In contrast, no statistically significant differences emerged in the comparisons involving the 50 - 59 age group. The data accentuates the significance of age disparities in mental adaptation among kindergarten teachers, particularly underscoring the contrast between the 40 - 49 age group and the 20 - 29 age group, emphasizing age as a crucial factor affecting mental adaptation levels.